Building tractable disjunctive constraints - Cohen, D; Jeavons, P; Jonsson, P; Koubarakis, M (2000)
Many combinatorial search problems can be expressed as 'constraint satisfaction problems'. This class of problems is known to be NP-hard in general, but a number of restricted constraint classes have been identified which ensure tractability. This paper presents the first general results on combining tractable constraint classes to obtain larger, more general, tractable classes. We give examples to show that many known examples of tractable constraint classes, from a wide variety of different contexts, can be constructed from simpler tractable classes using a general method. We also construct several new tractable classes that have not previously been identified. © 2000 ACM.